An analysis of trends and policies supporting alternative fuels for road freight transport in Europe - Gómez Vilchez, Jonatan J.; Julea, Andreea; Lodi, Chiara; Marotta, Alessandro (Frontiers in Energy Research, 2022)
A significant proportion of transport greenhouse gas emissions originates from the activity of light-duty trucks and heavy-duty vehicles. The overarching aim of this study is to assess road freight transport decarbonization in Europe by analyzing relevant trends (recent developments and future estimates) and policies. Specifically, the paper investigates the policy measures in place or introduced in the European Union Member States plus the United Kingdom between 2016 and 2018, as reported in their submissions to the European Commission, the market progress and status until 2020/1 and the techno-economic barriers that slow down further emissions mitigation. The study focuses on electric vehicles (battery electric and plug-in hybrid), fuel cell electric vehicles and natural gas-powered vehicles. We find wide differences in the strength of policy support by country, mode and fuel. Our analysis is constrained by data availability and we highlight the need for improvements in data reporting by countries, including the communication of future vehicle estimates and infrastructure targets. We reach the conclusion that, despite some progress, stronger action is needed to timely decarbonize road freight transport in Europe.